2012
DOI: 10.1021/ja302601f
|View full text |Cite
|
Sign up to set email alerts
|

Nonamorphism in Flufenamic Acid and a New Record for a Polymorphic Compound with Solved Structures

Abstract: The unprecedented polymorphism of the non-steroidal anti-inflammatory drug (NSAID) flufenamic acid (FFA) is described here. Nine polymorphs were accessed through the use of polymer-induced heteronucleation (PIHn) and solid-solid transformation at low temperature. Structural elucidation of six of these forms, in addition to the two previously known forms, makes FFA indisputably octamorphic. Although the structure of at least one other form of FFA remains elusive, the occurrence of most of these polymorphs under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(257 citation statements)
references
References 40 publications
10
243
3
1
Order By: Relevance
“…It has been reported that FFA has up to nine different crystal forms, among which FFA I (white colour) and FFA III (yellow colour) are the most commonly encountered. 35 Below a temperature of 42°C FFA III is the most stable form and has a lower solubility than its metastable form of FFA I, although the solubility difference between the two forms is very 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 small with less than 1 µg/mL. 37 Precipitation of the solid FFA III during dissolution under non-sink conditions shown in Figure 9(c) demonstrated that the supersaturation was first generated by the FFA-NIC CO dissolution and then followed by precipitation of the stable form FFA III.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FFA has up to nine different crystal forms, among which FFA I (white colour) and FFA III (yellow colour) are the most commonly encountered. 35 Below a temperature of 42°C FFA III is the most stable form and has a lower solubility than its metastable form of FFA I, although the solubility difference between the two forms is very 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 small with less than 1 µg/mL. 37 Precipitation of the solid FFA III during dissolution under non-sink conditions shown in Figure 9(c) demonstrated that the supersaturation was first generated by the FFA-NIC CO dissolution and then followed by precipitation of the stable form FFA III.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication reevaluating the chemical structure of FFA demonstrated that this molecule possesses at least nine polymorphs (Lopez-Mejias et al ., 2012), which may influence the bioavailability of the drug and thus provide new opportunities for the investigating the channels types targeted by FFA, depending on these polymorphs.…”
Section: Using Flufenamic Acid In Researchmentioning
confidence: 99%
“…It should be noted that similar phenomenon was found only in metastable polymorphic forms IV, VI, VIII of pure FFA. 9 Table 3 shows a comparison of the FFA conformations in the co-crystal with the most stable polymorphs I-III and the known co-crystals.…”
Section: Conformational Analysis and Crystal Packing Similaritymentioning
confidence: 99%
“…7 Five polymorphs of tolfenamic acid (TFA) have been reported, 8 whereas flufenamic acid (FFA), with nine polymorphic forms, is one of the most polymorphic drugs ever known. 9 However, niflumic acid (NFA) and N-phenylanthranilic acid (N-PA) are two exceptions. Recently, a new form II of NFA was obtained by Bag and Reddy who used the fast evaporation method, although its crystal structure was not determined.…”
Section: Introductionmentioning
confidence: 99%